Pengaruh Pemberian Infusa Temulawak (Curcuma xanthorrhiza Roxb.) Terhadap Berat Uterus Pada Tikus Putih (Rattus norvegicus) Postpartum - Dzakiyah, Nuha Uliya; Kalsum, Umi; Indahwati, Lilik (Journal of Issues in Midwifery, 2019)
Puerperal period is the period after childbirth until the organs recover as before preganancy, where one of the important sequences during the puerperium period is uterine involution. Involution of the uterus reflects changes in the shape and position of the uterus that affect the decrease in uterus size. Temulawak is one of native plants in Indonesia and widely used as a traditional medicine. This plant is also believed to improve postpartum health and suspected to have synergistic effect with the involution of the uterus.The purpose of this research is to know the influence of giving infusa temulawak (Curcuma xanthorrhiza Roxb.) to the uterine weight in rats (Rattus norvegicus) that had been given birth.  Experimental study using Post Test Only Control Group Design with female rats who have given birth and are breastfeeding. The sample is divided into four groups, that is one the control group and three for treatment groups given infusa temulawak with dosage concentrations of 10%, 20%, and 40%. The results was tested by One-way ANOVA and showed there was no significantly difference in uterine weight (p=0,139). The conclusions of this study is that giving the infusa temulawak quantitavely can lose weight of uterus rats at concentrations 10%, but there is not a statistically meaningful difference between groups.